Distinct Circle of Willis anatomical configurations in healthy preterm born adults: a 3D time-of-flight magnetic resonance angiography study - Greggio, J; Malamateniou, C; Baruteau, KP; Reyes-Aldasoro, CC; Huckstep, OJ; Francis, JM; Williamson, W; Leeson, P; Lewandowski, AJ; Lapidaire, W (BioMed Central, 2025)
Background: Preterm birth (< 37 weeks’ gestation) alters cerebrovascular development due to the premature transition from a foetal to postnatal circulatory system, with potential implications for future cerebrovascular health. This study aims to explore potential differences in the Circle of Willis (CoW), a key arterial ring that perfuses the brain, of healthy adults born preterm. Methods: A total of 255 participants (108 preterm, 147 full-term) were included in the analysis. High-resolution three-dimensional Time-of-Flight Magnetic Resonance Angiography (3D TOF MRA) datasets were analysed, measuring vessel diameters and classifying segments into different groups of CoW anatomical variations. Statistical comparisons assessed the prevalence of each variant group between preterm and full-term populations, as well as the relationship between CoW variability, sex, and degree of prematurity. Results: We identified 164 participants with variant CoW configurations. Unilateral segment hypoplasia (30%) and unilateral segment absence (29%) were the most common variations, with over 50% related to the posterior communicating artery (PComA). However, the incidence of absent segments was lower in preterm adults, who were more likely to exhibit variants associated with complete CoW configurations compared to full-term adults (p = 0.025). Preterm males had a higher probability of a group 1 variant (circles with one or more hypoplastic segments only) than the full-term group (p = 0.024). In contrast, preterm females showed higher odds of a group 4a variant (circles with one or more accessory segments, without any absent segments) in comparison to their full-term counterparts (p = 0.020). Conclusions: Preterm birth is linked to a distinct vascular phenotype of CoW in adults born preterm, with a higher likelihood of a CoW configuration with hypoplastic segments but a lower likelihood of absent segments. Future work should focus on larger prospective studies and explore the implications of these findings for normal development and cerebrovascular disease. Furthermore, TOF MRA might be a useful adjunct in the neurovascular assessment of preterm-born individuals.